Student’s informedness as a criterion of culture level - V.N. Stegniy (Высшее образование в России)
Student’s informedness is considered as an indicator of his culture level. Means, channels, sources of obtaining information by the student are discussed. The interrelation between the student’s informedness level and his progress in studies is traced.